Sistem Informasi Kalkulasi Bahan Baku Berbasis Mobile pada PT. Sari Burger Indonesia - Welda, Welda; Kusuma, Aniek Suryanti; Nuarta, I Ketut Pasek (INFOTEKS (Information Technology, Computer and Sciences), 2021)
PT. Sari Burger Indonesia, with one of its branches, is located at Jl. Teuku Umar, Level 21 Shopping Mall, Denpasar Bali. In realizing the company's goals by simplifying the process of calculating raw materials to be purchased by the company, there is a manager or, more precisely, an assistant manager in charge of calculating the raw materials to be purchased. This system is made using Data Flow Diagrams (DFD) design; this system is made based on Android, using android studio software, and with the help of Firebase, which has many readily available features, besides that this system uses the SMA (Single Moving Average) method. , this method is used during the forecasting calculation process. With this system, the goal of calculating the number of raw materials to be purchased becomes easier. The calculation process that was previously manual can now be easier to use a computerized system based on Android because the data inputted will be stored in the system in performing calculations. In addition, calculations that have been saved can also be downloaded using a file with a pdf extension. The system can also forecast the remaining stock, which will be used in estimating the amount of stock remaining next month.